Assessing Voltage and Frequency Instability in Renah Kemumu's Micro Hydro Power Plant - Tessal, Dasrinal; Candra, Joko; Manab, Abdul; Corio, Dean (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
The increasing demand for energy and the need for environmental sustainability have led to the adoption of renewable energy sources, such as micro-hydropower plants (PLTMH), in isolated communities in Indonesia. However, voltage and frequency instability issues are commonly encountered in PLTMH systems, which undermine their performance. In 2009, a micro-hydropower plant with a capacity of 30 KW was built in Renah Kemumu village. Ranah Kemumu village is located in Jangkat sub-district, Merangin district, Jambi province. In this study, the voltage and frequency instability of PLTMH in Renah Kemumu Village were investigated. The methodology employed in this study was observational. The voltage and frequency data were measured and recorded during peak load hours from 18.00 to 21.00 over one month. The percentage increase relative to the standard voltage and frequency was calculated. Boxplots were generated to visualize the distributions. The voltage measurements showed maximum and minimum values of 270 V and 264 V, representing increases of 22.72 % and 20.45% from the 220 V (standard set by the power utility (PLN)). The frequency ranged from 66.32 Hz to 57.46 Hz, corresponding to 30.92% and 14.92% deviations from the 50 Hz (standard set by the power utility (PLN)). These values exceeded the tolerance limits of the State Electricity Company of Indonesia. The analysis indicates that the voltage and frequency levels at the PLTMH in Renah Kemumu Village are unstable during peak loads, with fluctuations stemming from changing water flows, load currents, and weather conditions